Antidepressants inhibit P2X4 receptor function: a possible involvement in neuropathic pain relief - Tozaki-Saitoh Hidetoshi; Tsuda Makoto; Yamashita Tomohiro; Imai Toshiyasu; Nagata Kenichiro; Inoue Kazuhide (SAGE Publishing, 2009)
Abstract Background Neuropathic pain is characterized by pain hypersensitivity to innocuous stimuli (tactile allodynia) that is nearly always resistant to known treatments such as non-steroidal anti-inflammatory drugs or even opioids. It has been reported that some antidepressants are effective for treating neuropathic pain. However, the underlying molecular mechanisms are not well understood. We have recently demonstrated that blocking P2X4 receptors in the spinal cord reverses tactile allodynia after peripheral nerve injury in rats, implying that P2X4 receptors are a key molecule in neuropathic pain. We investigated a possible role of antidepressants as inhibitors of P2X4 receptors and analysed their analgesic mechanism using an animal model of neuropathic pain. Results Antidepressants strongly inhibited ATP-mediated Ca2+ responses in P2X4 receptor-expressing 1321N1 cells, which are known to have no endogenous ATP receptors. Paroxetine exhibited the most powerful inhibition of calcium influx via rat and human P2X4 receptors, with IC50 values of 2.45 μM and 1.87 μM, respectively. Intrathecal administration of paroxetine produced a striking antiallodynic effect in an animal model of neuropathic pain. Co-administration of WAY100635, ketanserin or ondansetron with paroxetine induced no significant change in the antiallodynic effect of paroxetine. Furthermore, the antiallodynic effect of paroxetine was observed even in rats that had received intrathecal pretreatment with 5,7-dihydroxytryptamine, which dramatically depletes spinal 5-hydroxytryptamine. Conclusion These results suggest that paroxetine acts as a potent analgesic in the spinal cord via a mechanism independent of its inhibitory effect on serotonin transporters. Powerful inhibition on P2X4 receptors may underlie the analgesic effect of paroxetine, and it is possible that some antidepressants clinically used in patients with neuropathic pain show antiallodynic effects, at least in part via their inhibitory effects on P2X4 receptors.